Metode Analityc Hierarchy Process Dan Promethee Untuk Merekomendasikan Pemilihan Perguruan Tinggi Cirebon - Yuhano; Nurokman (STIKOM POLTEK CIREBON, 2023)
In determining Cirebon tertiary institutions at SMAN 1 Lemahabang. The selection process is carried out by comparing alternatives in each tertiary institution based on predetermined criteria. The number of criteria that must be assessed at each tertiary institution made it difficult for the selection team. Furthermore, many problems arise due to frequent changing assessments. The combination of the Analytical Hierarchy Process (AHP) method and Preference Ranking Organization Method for Enrichment Evaluation (Promethee) was carried out because these two methods are able to solve problems with many criteria. The criteria used are assessment data from guidance and counseling teachers in tertiary institutions, namely campus accreditation, number of lecturers, tuition fees, departments and campus facilities. The result is that IAIN Syekh Nurjati can be recommended by universities in Cirebon for students to continue their education, because it is different from other universities and has a value of 0.263; Gunung Djati Swadaya University (Unswagati) is recommended by private universities (PTS) in Cirebon as the choice of students in continuing to higher education in the field of education with a score of 0.184; and STIKOM Cirebon Poltek recommended PTS in Cirebon as the choice of students in continuing to higher education in the field of information technology-based campuses with a value of 0.080 greater than the others